Comparing Gingival Crevicular Fluid Visfatin Levels Between Patients with Endometrial Cancer and Chronic Periodontitis and Healthy Controls - Mohammad Moazen; Mojtaba Bayani; Mina Ranjbar; Mehrzad Shaddel; Madihe Amini; Ashraf Zamani (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: The association between periodontal diseases and endometrial cancer (EC) has been assessed in some studies but the probable role of inflammatory factors such as visfatin is unknown. This study aimed at evaluating the levels of visfatin in gingival crevicular fluid (GCF) in patients with EC and chronic periodontitis (CP) to address this gap. Materials and methods: In a case-control study with matched age and body mass index controls, 120 female participants were divided into four groups. Case groups included group I (EC-CP [n=20]), group II (EC without CP [n=20]), and controls were group III (without EC but diagnosed with CP [n=40]), and group IV (healthy without EC or CP [n=40]). GCF samples were collected and visfatin was assessed by enzyme-linked immunosorbent assay. Results: Clinical periodontal parameters such as periodontal pocket depth, clinical attachment loss, and bleeding on probing were significantly higher in EC-CP group than other groups (P<0.001). Mean visfatin level in GCF was found to be significantly different in group I compared with groups II and IV (P<0.001). Also, there was a significant difference in visfatin concentration in GCF between group III and group IV (P<0.001). Conclusion: According to current study, GCF visfatin concentration is probably associated with EC and CP.